Analisis perhitungan harga pokok produksi dengan metode full costing dan variable costing dalam menentukan harga jual - Ramdaniyati, Siti (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study aims to analyze the comparison between the calculation of production costs using the full costing method, the variable costing method, and the cost plus pricing method in determining the selling price at the Amanah Factory. In this study, the researcher used a quantitative descriptive approach with the type of research, namely a case study. The types of data used by the researcher are qualitative data and quantitative data, with the data sources used being primary data and secondary data. The data analysis technique used in this study is descriptive statistics. The results of the study showed that the calculation of the company's selling price was lower than the selling price from the analysis results using the cost plus pricing method with the full costing approach and the variable costing approach. It can be concluded that there is a difference in the cost of production and the selling price with the full costing and variable costing methods.